Good Financial Planning Considering the Exchange Rate Fluctuation - Cordelia Alisbha; Ibtisam Abnaty Intishar (Journal La Bisecoman, 2020)
The study discusses planning a management function, the success or failure of achieving predetermined goals depends on planning The financial planning process rate and political stability in saving money, Two important aspects in the financial planning process (1) Cash planning, which includes the preparation of the company's cash budget. (2) Profit planning, corporate profit planning made in the form of a pro forma financial report. Interest rate, changes in interest rates will affect the value of a country's currency in general against the dollar. Currency trading rates (forex), interest rates, and inflation are all interrelated. An increase in the interest rate causes a country's currency to appreciate. Political Stability the political stability and economic performance of a country can affect the strength of its currency.